Novel Fertilizer as an Alternative for Supplying Manganese and Boron to Soybeans. Issue 1 (2nd January 2019) - Baxter, Abigail E.; Maguire, Rory O.; Whitehurst, Garnett; Holshouser, David; Reiter, Mark
ABSTRACT: Soybean ( Glycine max ) commonly experience Mn deficiencies in the coarse-textured soils of Coastal Plain Virginia, especially under high pH conditions. The objective of this study was to investigate the ability of a novel coated fertilizer to provide Mn and B to soybeans in soils where Mn deficiency is common and B deficiency, although far less common than with Mn, is possible. A 60-d greenhouse experiment was conducted with three treatments: control, uncoated KCl, and Mn +B coated KCl applied to Bojac and Dragston sandy loams. Soil and whole plant tissue samples were collected throughout the experiment. Bojac and Dragston soils treated with the coated KCl contained 12.0 mg kg −1 and 15.8 mg kg −1 more Mehlich 1 – Mn, 21.7 mg kg −1 and 23.0 mg kg −1 more Mehlich 3 Mn, and 4.5 mg kg −1 and 4.6 mg kg −1 CaCl2 – Mn than the control and uncoated KCl, respectively. Coated KCl increased above ground tissue Mn by 42.9 mg kg −1 compared to the control and the uncoated KCl treatments in the Bojac soil, while the Dragston soil showed no significant differences in Mn tissue concentration between treatments. Above ground tissue, Mn was much lower in the Dragston soil than the Bojac, probably due to greater organic matter which chelates Mn keeping it less plant available. Boron concentrations did not differ in plant tissue or soil, regardless of the extraction method. Results indicate that the coated KCl product could consistently provide increased Mn concentration in acidic sandy soils despite varying levels of organic matter, but is not effective for B.